Haploidentical, matched-related, and matched-unrelated hematopoietic cell transplant for acute leukemias in the early years of haploidentical transplant implementation in a developing country with a large unrelated donor registry - Seber, Adriana; Arcuri, Leonardo Javier; Colturato, Vergilio Rensi; Souza, Mair Pedro; Zogbi, Yana Augusta Novis; Funke, Vaneuza; Lerner, Decio; Macedo, Maria Cristina; Daudt, Liane; Kerbauy, Mariana Nassif; Zecchin, Victor Gottardello; Duarte, Fernando Barroso; et al. (Frontiers in Oncology, 2025)
IntroductionOver the last decades, the donor network for hematopoietic cell transplantation (HCT) has grown exponentially, including unrelated and haploidentical (Haplo) donors. This study aimed to describe HCT outcomes with MSD, Haplo, and matched unrelated donors (MUD) in an early period of Haplo with posttransplant cyclophosphamide in a developing country with a large unrelated donor registry.MethodsThis study was conducted in collaboration with the CIBMTR. We included patients with acute leukemias undergoing HCT between 2014-2018.ResultsWith 595 patients, 2-year overall survival (OS) was 69% for the MSD, 65% for the Haplo, and 71% for MUD (p=0.24) in CR1, confirmed in multivariable analysis. Relapse rate was lower for MUD (HR=0.35, p=0.0005) than MSD in patients with CR2+, leading to higher OS. Relapse was also higher with Haplo compared with MUD (HR=2.06, p=0.03).DiscussionOnly survival bias can explain these findings in CR2+, suggesting some high-risk MUD patients, in which HCT timing is crucial, may not achieve HCT. Alternative donors were associated with higher non-relapse mortality, while PTCy-based Haplo offered the best protection against chronic graft-versus-host disease. Our study suggests Haplo and MUD are acceptable options for patients lacking MSD in developing countries like ours.